Proyecto de factibilidad para la creación de una empresa para el alquiler de canchas de futbol de cesped sintético en la parroquia Sangolquí, cantón Rumiñahui, provincia de Pichincha - Valarezo Tixi, Jorge Mauricio (2015)
Physical exercise improves mental function, autonomy, memory, speed, "body image" and the feeling of wellbeing, stability in personality characterized by optimism, euphoria and mental flexibility occurs. Physical activity programs should provide relaxation, endurance, muscular strength and flexibility. In the interaction of the body with the space and time through movement, numerous human learning are built. This construction is done through a series of educational experiences that are promoted through exploration, practice and internalization and structuring the body scheme called. That is whyin this researchisthe general objective, conduct afeasibility projectfor the creationof a company tohirefootball fieldssynthetic grassin the ParishSangolquí, Canton Rumiñahui, PichinchaProvince; in order tomeettheneeds and preferencesof existinglocal peoplerequiring this typeof service as ameans ofdistraction forchildren and youthof the county. In this research process, the following aspects are analyzed: Inthe Methodologyresearch methodsaredescribedasinductive, deductive, descriptive, analytical and statistical methods; as well asdirect observationand survey, itwas appliedto400 inhabitantsconsideredeconomically activepopulationagedSangolquíParishbetween 18and 65 years ofage, witha total of84,897inhabitants. The Market, allowed to gather information from the survey population, using surveys and their respective statistical tabulation and analysis, determining consumer preferences and demand to know the existing supply, resulting as unmet demand for the first year of 93,078 services annually. The size and location of the plant set the installed capacity of 4,344 annual service, which means 4.71% attention to the market; the place for the operation of the soccer artificial turf, will all basic facilities and parking. The systems and processes to the service, the structural design of the plant and the establishment of human, material and financial resources necessary for the operation of the company, were determined in the project engineering In the financial analysis shows that the project requires an investment of $ 67.355,04 of which 53,64% will be financed with a bank loan, the rest is done with equity partner company in the amount of $ 31.236,91. Has established the technical structure - for handling administrative and administrative operation of the company where there is a list of 5 people including managers and employees. Financial evaluation was performed using financial indicators in which a Net Present Value (NPV) positive result of $ 8.707,45 was obtained; the Benefit - Cost, indicated that for every dollar invested, a return of 80 cents more is obtained; IRR gives a percentage of 12,93%; Recovery Period noted that the investment is recovered in 3 years, 6 months and 4 days; with sensitivity analysis, increasing costs by 31,20% sensitivity coefficient of 0.99 is obtained and reducing revenues by 17.32%, 0.99% is obtained .What means that despite these changes the project is not sensitive and can withstand such changes. It issued before we can conclude that the project is profitable and therefore its implementation is feasible. Finally the conclusions and recommendations that have been reached, with different approaches to the project itself are presented, which let you raised with proper underpinnings that it deserves; not before recommending to students, professionals and stakeholders analysis and interest in this type of very important projects for socio-economic development of Rumiñahui Canton